2013
DOI: 10.1123/ijsc.6.4.409
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Women in Sport-Talk Radio: A Survey of Directors

Abstract: Sport-talk radio has been recognized, along with other forms of sports media, as a masculine space where women’s value as athletes and fans is diminished. Little is known, however, about the gendered dynamics of sport-talk-radio production. This study used a survey of programming directors from across the United States to explore issues around the employment of women and coverage of women’s sport by local stations. Results suggest that many stations do not employ any women, although more than half do. Still, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A common perception in the sports industry is that audiences, viewers, and fans are inherently not interested in women’s sports (Hardin et al 2013), and gender-bland sexism reflects and reinforces this postfeminist sensibility. Gender-bland sexism explains the lack of coverage of women’s sports and the poor quality of coverage not as sexism on the part of (mostly male) sports commentators but in terms of the market-based logics of supply and demand (Bonilla-Silva 2006, 2012; Gill 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A common perception in the sports industry is that audiences, viewers, and fans are inherently not interested in women’s sports (Hardin et al 2013), and gender-bland sexism reflects and reinforces this postfeminist sensibility. Gender-bland sexism explains the lack of coverage of women’s sports and the poor quality of coverage not as sexism on the part of (mostly male) sports commentators but in terms of the market-based logics of supply and demand (Bonilla-Silva 2006, 2012; Gill 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Even though engaging with sports is a favoured pastime for both men and women, prior studies have shown that women feel marginalised as sports fans (e.g., Gosling, 2007; Pope, 2017; Toffoletti & Mewett, 2012b). Women generally feel unwelcome in both online and offline sports discussions (e.g., Hardin, Antunovic, Bien-Aimé, & Li, 2013), and indeed, women have often been unwanted at sports events since the beginning of modern spectator sports. Schultz and Linden (2014) demonstrate that women were only welcome as spectators to American sports under strict conditions—either as moral agents to calm down the unruly men or as consumers filling up the stands (Fink, Trail, & Anderson, 2002).…”
mentioning
confidence: 99%
“…Further, the lack of women as NBC speakers (anchors, play-by-play announcers, color commentators or analysts, and reporters) indicates the sexism of the sports media industry (Arnold, Chen, & Hey, 2015; Hardin, Antunovic, Bien-Aimé, & Li, 2013). This is not a surprising finding considering the list of NBC Olympic commentators released by the network about a month before the games: Of the 128 play-by-play commentators, analysts, and reporters, only 28 were women (Zaccardi, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%